2014
DOI: 10.1177/0363546514541226
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Cruciate Ligament Graft Fixation Angles, Part 2

Abstract: This study found that all 6 fixation angle combinations significantly improved knee kinematics compared with the sectioned state at time zero; however, it is recommended that fixation of the PMB graft be performed at 0° because of the significant increases in PMB graft loading that occur with fixation at 15° and that fixation of the ALB graft be performed at 90° or 105° rather than 75° to minimize ALB graft forces, which could lead to graft attenuation or failure over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 22 publications
(29 reference statements)
3
37
2
3
Order By: Relevance
“…The long-held notion of PCL biomechanics was that the two bundles functioned independently, with the ALB acting primarily during flexion and the PMB in knee extension [1,17]. More recent research, however, suggests that the two bundles function synergistically [18][19][20][21]. Multiple studies have examined knee biomechanics by sectioning the PCL, which collectively demonstrate that an isolated tear of either bundle does not result in a clinically significant increase in posterior translation of the tibia [20,22].…”
Section: Biomechanicsmentioning
confidence: 99%
“…The long-held notion of PCL biomechanics was that the two bundles functioned independently, with the ALB acting primarily during flexion and the PMB in knee extension [1,17]. More recent research, however, suggests that the two bundles function synergistically [18][19][20][21]. Multiple studies have examined knee biomechanics by sectioning the PCL, which collectively demonstrate that an isolated tear of either bundle does not result in a clinically significant increase in posterior translation of the tibia [20,22].…”
Section: Biomechanicsmentioning
confidence: 99%
“…Sutures for the ALB bone plug of the quadriceps autograft are pulled into the respective femoral tunnel and fixed by a 9 × 20–mm titanium screw (Arthrex); screw placement is shown in Figure 6 . The graft is passed down the tibial tunnel, and the ALB graft is fixed first with the knee flexed to 90° 13 and secured using a 6.5 × 40–mm half-threaded, bicortical cancellous screw (Arthrex) as a post and an 18-mm washer (Arthrex). The PMB graft is then fixed to the tibia through the split tendon graft and with the knee in full extension using the screw and washer; tibial attachment screw placement is shown in Figure 7 .…”
Section: Techniquementioning
confidence: 99%
“…Describing a new technique with the use of two allografts, Spiridonov et al [ 19 ] reported excellent outcomes both when it comes to objectively measured stability and patient-reported outcomes. Later, biomechanical studies have shown superior results with the same DB PCLR technique compared to SB technique [ 7 , 20 ]. To our knowledge, there are no studies that have looked at the costs of the different treatment algorithms for treating PCL injuries.…”
Section: Introductionmentioning
confidence: 99%